Plasmodium vivax in Hematopoietic Niches: Hidden and Dangerous. Issue 5 (May 2020) - Silva-Filho, João Luiz; Lacerda, Marcus V.G.; Recker, Mario; Wassmer, Samuel C.; Marti, Matthias; Costa, Fabio T.M.
Abstract : Estimation of Plasmodium vivax biomass based on circulating biomarkers indicates the existence of a predominant biomass outside of the circulation that is not captured by peripheral parasitemia, in particular in patients with complicated outcomes. A series of recent studies have suggested that the hematopoietic niche of the bone marrow (BM) is a major reservoir for parasite replication and the development of transmission stages. However, significant knowledge gaps remain in our understanding of host–parasite interactions, pathophysiology, and the implications for treatment and diagnosis of such a reservoir. Here, we discuss the current status of this emerging research field in the context of P. vivax . Highlights: Peripheral parasitemia underestimates the total biomass of Plasmodium vivax, and there is no clear correlation of biomass with disease severity. Recent data demonstrate that P. vivax parasites expand outside of the circulation in the hematopoietic niche of the BM and possibly spleen. P. vivax infection in the BM niche may affect BM function and host immunity and result in chronic inflammation and other morbidities.